2013
DOI: 10.1021/ef4005175
|View full text |Cite
|
Sign up to set email alerts
|

Ash-Forming Matter in Torrefied Birch Wood: Changes in Chemical Association

Abstract: Torrefaction is heat treatment of biomass at relatively low temperatures (∼240–300 °C) in the absence of air. The torrefied fuel offers advantages to traditional biomass, such as higher energy density, better grindability, and reduced biological decay. These factors could, for example, lead to increased use of biomass in pulverized coal boilers. Ash-forming elements are present in biomass as water-soluble salts, ion-exchangeable elements, included or excluded minerals, and covalently bound sulfur and chlorine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 25 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…In comparison to the raw food wastes, almost no AAEM species are released during the torrefaction of the food wastes. However, it can be found that the transformation of AAEM species takes place during torrefaction, which is consistent with the results by Shoulaifar et al . During the torrefaction of LC and WP, almost no transformation of alkali metals is observed, while a portion of water-soluble K (12.1%) is transformed into CH 3 COONH 4 -soluble K during the torrefaction of LP.…”
Section: Results and Discussionsupporting
confidence: 91%
“…In comparison to the raw food wastes, almost no AAEM species are released during the torrefaction of the food wastes. However, it can be found that the transformation of AAEM species takes place during torrefaction, which is consistent with the results by Shoulaifar et al . During the torrefaction of LC and WP, almost no transformation of alkali metals is observed, while a portion of water-soluble K (12.1%) is transformed into CH 3 COONH 4 -soluble K during the torrefaction of LP.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The AC in the torrefied pruned Oxytree biomass ranged from 7% to 1% [19]. This is a much higher value than that found in torrefied wood from torrefied pine 0.15%–0.21% [25] and birch 0.23%–0.38% [26]. The AC values obtained for Oxytree were closer to the corn stover 10%–12% [27].…”
Section: Discussionmentioning
confidence: 99%
“…The sources of the collected experimental data are also provided in Table 1. For instance, the torrefaction data for birch were obtained from four different sources [20][21][22][23][24] with a minimum and a maximum torrefaction temperature of 200 • C and 280 • C respectively, and the residence times varying between 10 and 60 min. Table 2 presents an overview of the compiled data based on the wood type including the number of measurements (n), the minimum (Min), maximum (Max), and mean of experimentally measured Y s , C, H, N contents, and the HHV.…”
Section: Biomass Samplesmentioning
confidence: 99%